The Role Of Technical Oversight In Banks In Money Laundering Operations: A Case Study At The National Bank Of Iraq - Dr. Raad Zaid Alwan (Academia Open, 2027)
Financial institutions face critical vulnerabilities from increasingly sophisticated financial crimes. Banking sectors globally encounter severe operational risks when detecting complex illicit fund flows through traditional surveillance frameworks. Prior research insufficiently addresses how internal technical infrastructure directly mitigates automated financial misconduct within private institutions. General Background Money laundering threatens global financial stability through increasingly complex digital networks. Specific Background Commercial banks act as primary lines of defense but face challenges due to weak supervisory technology and operational pressures. Knowledge Gap Empirical evidence evaluating how technical control systems directly influence anti-money laundering efficacy within private banking remains limited. Aims This study evaluates the statistical impact of internal technical oversight on money laundering prevention at the National Bank of Iraq. Results Regression analysis demonstrates that technical control systems exert a significant positive effect ($R^2 = 0.582, p < 0.001$) on combating illicit financial activities. Novelty The research establishes quantitative empirical metrics validating automated detection technology within Middle Eastern private banking operations. Implications Strengthening smart digital surveillance and specialized technical competencies is vital for institutional compliance and financial integrity. Keywords: Technical Oversight, Money Laundering Operations, Banking Compliance, Financial Risk, Detection Systems Key Findings Highlights Empirical regression analysis confirms a statistically significant direct impact of technical control infrastructure on mitigating money laundering operations ($R^2 = 0.582$). Advanced technical systems provide essential immediate automated alerts and identify abnormal financial transaction patterns within private banking operations. Heavy daily employee workloads and specialized personnel shortages represent critical operational bottlenecks that reduce supervisory compliance effectiveness.